Comparative Study of the Preparation of Reducing Sugars Hydrolyzed from High-Lignin Lignocellulose Pretreated with Ionic Liquid, Alkaline Solution and Their Combination - Sangian, Hanny F.; Kristian, Junaidy; Rahma, Sukma; Agnesty, Silvya Yusnica; Gunawan, Setiyo; Widjaja, Arief (Journal of Engineering and Technological Sciences, 2015)
The ionicliquid [MMIM][DMP] was synthesized from the reactants methyl imidazole [MIM] and trimethylphosphate [TMP] and verified using 1HNMR and FTIR. Coconut coir dust was pretreated with a 1% alkaline solution.Its crystalline structure increased significantly due to the dissolution of lignin and hemicelluloses under alkaline conditions, exposing the cellulose. After NaOH and IL were employed, the XRD showed that peak (002) decreased significantly and peak (101) almost vanished. This significant decrease in crystallinity was related to the alteration of the substrate from the cellulose I structure to the cellulose II structure. The pretreated substrates were hydrolyzed to convert them to reducing sugars by pure cellulase and xylanase,and the reaction was conducted at 60Â°C, pH 3, for 12 or 48 hours. The yields of sugar hydrolyzed from untreated and NaOH-pretreated substrates were 0.07 and 0.12 g sugar/g lignocellulose, respectively. Pretreatment with IL or the combination of NaOH+IL resulted in yields of reducing sugars of 0.11 and 0.13 g/g, respectively. These findings showed that IL pretreatment of the high-lignin lignocellulose is a new prospect for the economical manufacture of reducing sugars and bioethanol in the coming years.